Occupational stress and coping strategies of the nursing staff of a Public University Hospital during the COVID-19 pandemic - Zacharenia Dimitriadou; Petros Kostagiolas; Georgios Kritsotakis; Nikos Rikos; Areti Stavropoulou; Michael Rovithis (Tehran University of Medical Sciences, 2023)
Background & Aim: Nursing staff are exposed to high levels of stress daily due to the demanding work environment. This study aimed to examine nursing staff occupational stress and coping mechanisms during the COVID-19 pandemic.‎ Methods & Materials: A cross-sectional study with a sample of 108 nursing staff was carried out. The Expanded Nursing Stress Scale (ENSS), the Brief Coping Orientation to Problems Experienced (Brief COPE) Scale, and constructed questions were used for data collection. Data were analyzed using chi-square (χ2), Pearson methods, and Multiple linear regression analysis. Statistical significance was determined at p-value ≤ 0.05. Results:  Overall Occupational stress was assessed with a mean score of 146.8 (SD±35.3). In Brief COPE Scale higher mean was assessed for "social support - information seeking" and lower for "substance use" or "withdrawal" (p<0.001). A significant difference in response distributions was observed regarding their degree of concern or fear about COVID-19 (p<0.01). Increased levels of Overall Occupational Stress (ENSS) were associated with higher levels of BCOPE. Emotional Focus and Venting and Diffusion of Emotions (β=5.15, p=0.026), younger age of the participants (β=-5.78, p=0.033), years of working in the healthcare sector (β=14.46, p=0.004) or the highest fear/concern about being infected and infecting their patients (β=6.22, p=0.032). Conclusion: Nursing staff experienced moderate levels of occupational stress, while challenges raised by the pandemic were handled through seeking social support, positive reframing and acceptance, taking protective measures, and turning to religion. Developing meaningful administrative and educational strategies for staff empowerment and resilience may reduce anxiety and occupational stress for nurses.